PERAN TEORI TAGMEMIK DALAM PEMBELAJARAN SASTRA ANAK KHUSUSNYA PENGGUNAAN MEDIA LAGU-LAGU DOLANAN - Husin, Ahmad; Husin, Roihanah (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2015)
A comprehensive approach in analyzing children's literature associated with the study of linguistics is tagmemic theory. Due to the broadness of this approach coverage, this paper will limit to a famous linguistic flow has appeared in America. The new stream is called Tagmemic. This stream was introduced by Kenneth Lee Pike, an activist of the Summer Institute of Linguistics (SIL), which is associated with the Wycliff Bible Translators, Bible translator organization into various languages . Tagmemics theory pioneer, Kenneth Lee Pike,was a Protestant priest and linguistic expert who co-founded and developed the SIL. As a Christisn priest, Pike devotedhis life to teaching activities, spreading the gospel and translating the Bible into languages that have never heard of this book. As a scholar, Pike dedicated himself in the field of research and the development of language. Tagmemics theory evolved to a more comprehensive theory of language within the scope of human behavior developed by Pike in 1954-1960.Keywords: tagmemic, language, children literature